Arthur B. Spingarn papers - Spingarn, Arthur B. (Arthur Barnett), 1878-1971.
Correspondence, memoranda, minutes of meetings, wills and estate files, reports, briefs, hearing and trial transcripts, and other papers relating chiefly to Spingarn's service with the National Association for the Advancement of Colored People (NAACP) as vice president, chairman of the legal committee, and president (1911-1965).
The collection pertains primarily to civil rights issues; financial, legal, and other administrative matters of the NAACP; relations between NAACP directors and officers including W. E. B. Du Bois, James Weldon Johnson, Mary White Ovington, William Pickens, Walter Francis White, and Roy Wilkins; the origin of the NAACP Legal Defense and Educational Fund; the official organ of the NAACP, The Crisis; the New York Vigilance Committee (later the New York branch of the NAACP); and Spingarn's work with the American Social Hygiene Association, Circle for Negro Relief, New York State Commission Against Discrimination, and New York Tuberculosis and Health Association. Topics include the East St. Louis riot of 1917; the assault on NAACP officer, John R. Shillady, in 1919; American occupation of Haiti in the 1920s; African American troops in World War II; and writings by native Africans.
Correspondents include Van Wyck Brooks, James A. Cobb, W. E. B. Du Bois, Ernest Gruening, Alfred Baker Lewis, Isadore Maximilian Martin, Lewis Mumford, Herbert J. Seligmann, Charles H. Studin, Neval Thomas, Carl Van Vechten, Walter Francis White, and Roy Wilkins.
Microfilm edition of materials received prior to 1988 available
Microfilm produced from originals in the Manuscript Division.
Library of Congress Prints and Photographs Division.
Civil rights leader and lawyer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Brooks, Van Wyck, -- 1886-1963 -- Correspondence; Cobb, James A. -- 1876-1958 -- Correspondence; Du Bois, W. E. B. -- 1868-1963 -- Correspondence; Gruening, Ernest, -- 1887-1974 -- Correspondence; Johnson, James Weldon, -- 1871-1938 -- Correspondence; Lewis, Alfred Baker, -- 1897 -- Correspondence; Martin, Isadore Maximilian, -- 1909- -- Correspondence; Mumford, Lewis, -- 1895-1990 -- Correspondence; Ovington, Mary White, -- 1865-1951 -- Correspondence; Pickens, William, -- 1881-1954 -- Correspondence; Seligmann, Herbert J. -- 1891- -- Correspondence; Shillady, John R., -- 1875-1943 -- Correspondence; Studin, Charles H. -- Correspondence; Thomas, Neval -- Correspondence; Van Vechten, Carl, -- 1880-1964 -- Correspondence; White, Walter Francis, -- 1893-1955 -- Correspondence; Wilkins, Roy, -- 1901-1981 -- Correspondence; New York (State). -- State Commission Against Discrimination; American Social Hygiene Association; Circle for Negro Relief; NAACP Legal Defense and Educational Fund; National Association for the Advancement of Colored People; New York Committee of Vigilance; New York Tuberculosis and Health Association; Crisis; African literature; African Americans -- Civil rights; African Americans -- Societies, etc; Civil rights; Riots -- Illinois -- East Saint Louis; World War, 1939-1945 -- Participation, African American; Haiti -- History -- American occupation, 1915-1934.; Civil rights leaders; Lawyers